Revolusi Pendidikan: Kurikulum Merdeka Solusi Problematika Belajar? - Vahira Febri Herina Putri; Masduki Asbari; Salma Adzka Khuzaima Khanza (Journal of Information Systems and Management (JISMA), 2023)
The purpose of this study is to deepen understanding, and introduce innovations in learning methods that give students the freedom to explore, collaborate and create solutions. This study report uses a descriptive qualitative method by doing simak catat because the data source is obtained by listening to the oral narration from the Youtube channel Sobat Baru entitled "Is it true that we are already free to learn?" presented by  Rocky Gerung. The results of this study explain that Indonesia has implemented an independent learning system but basically it is not fully independent. This research begins with the emergence of many problems in the world of education, which raises the question "Is it true that we are truly free to learn?". This problem is happening until now and can change the way a person thinks in living life.